Design and Development of a Web-Based Information System for Sapta Kanda Ramayana Using the Laravel Framework - Arnawa, I Putu Riko Putra; Sudana, Anak Agung Kompiang Oka; Putra, Yogiswara Dharma (Program Studi Pendidikan Teknologi Infromasi UMK, 2026)
The Ramayana is a story written by Rsi Valmiki that consists of seven parts called Sapta Kanda. The Ramayana is a cultural heritage rich in knowledge, but faces accessibility challenges in the modern era. This study contributes a novel web-based platform specifically designed to digitize and disseminate the Sapta Kanda Ramayana, integrating bilingual content (Old Javanese and Indonesian) with multi-role user interaction—an approach not found in prior cultural information systems. This development aims to design a website-based information system that can present the Sapta Kanda Ramayana story through a digital and interactive platform. The Laravel framework makes the system development process more structured and efficient. The system development uses the waterfall method, which goes through a series of processes such asnalysis, design, implementation, and testing, so that the system development process runs smoothly. The resulting system includes features for managing Sapta Kanda content, Ramayana characters, and user-contributed content. System testing uses the black box testing method to test system functionality and usability testing with the System Usability Scale (SUS) method to determine user satisfaction levels. The results of the system testing showed that the functionality of the features in the system worked well through black box testing and obtained a score of 85.4 from 21 respondents through testing using the SUS method, which indicates that the developed system is well accepted by users. This study is limited to web-based access and does not yet cover mobile application deployment or offline accessibility.